Libraries and reading : intellectual disability and the extent of library diversity - Conner, Matthew; Plocharczyk, Leah (Emerald Publishing Limited, 2020)
Libraries are supposed to serve all people in the community, but some still struggle to provide support for those with intellectual and developmental disabilities (IDD). In an age of increasing social consciousness and awareness of diversity, individuals with IDD deserve the greatest attention and support to achieve equality, yet how to do so remains a legitimate question as most library services are not yet prepared to offer the help needed. In Libraries and Reading, expert authors Matthew Conner and Leah Plocharczyk examine the modern history of libraries and diversity, the recent legislative history of those with IDD such as No Child Left Behind and mainstreaming policies; learning theories such as social constructivism, cognitivism, preliteracy, and Universal Design for Learning; and case studies of library outreach around the globe. Including real-world examples, they show how we can make big changes through small steps. In a climate of tightened budgets and severe demands on public literacy resources, the moral imperative of helping those with IDD runs up against practical barriers. Conner and Plocharczyk go to the foundations of social justice in Cultural Studies to show how the means of integrating those with disabilities into libraries and communities can be found in our everyday practices.